Piecewise parameter estimation for stochastic models in COPASI - Bergmann, Frank T.; Sahle, Sven; Zimmer, Christoph (Bioinformatics, 2016)
Abstract. Motivation: Computational modeling is widely used for deepening the understanding of biological processes. Parameterizing models to experimental data
Gesehen am 07.05.2020